Pillow Book Media as Dental Health Promotion in Preschool Children: is it effective? - Ngatemi; Lestari, Syifa Yulia; Suwarsono; Purnama, Tedi (International Journal Of Drug Research And Dental Science, 2022)
Background: The main problem in dental health and in preschool children is dental caries, where the prevalence of dental caries in children aged 5-6 years is 92.6% with a def-t index of 8.43. One of the causes of high dental health problems is low tooth brushing behavior and preschool children do not yet have the independence in brushing their teeth. It is proven that the data on the behavior of brushing teeth correctly is only 2.3%. Efforts to improve the dental health of preschool children by providing dental health education. Media pillow book is a development of booklet. The media pillow book is made of cloth containing pictures and writings about maintaining dental health which aims to increase creativity and cognitive abilities and skills of preschool children in maintaining dental health.Material and Methods: This study uses a quasi-experimental design with a pretest and posttest with one group design. This research was conducted at Bintang Kindergarten, Cilandak District, South Jakarta City. Independent variable: pillow book media and dependent variable: knowledge and skills of brushing teeth of preschoolers. Data were tested using Wilcoxon.Results: Pillow book media proved to be significantly (p<0.001) effective in increasing the knowledge and skills of brushing teeth of preschoolers.Conclusion: Pillow book media is effective as promotion of dental health in increasing knowledge and skills of brushing teeth of preschool children.